Factors Affecting The Exchange Rate Volatility In Asean Four - Ishak, Samsudin (2008)

(untitled)
Regional integration has become important subject among economists and is viewed capable of boosting monetary cooperation and foreign exchange arrangements among ASEAN members thus promotes greater macro coordination, with the ultimate goal of reducing the extent of macroeconomics volatility such as exchange rate volatility. The purpose of the formation is to reduce exchange rate uncertainty and to avoid exchange rate misalignment among the ASEAN member countries namely; Indonesia, Malaysia, Thailand, and The Philippines. This thesis intends to investigate the extent of optimum currency area (OCA) criteria and financial factors (FF) works within the context of ASEAN region with US Dollar and Japanese Yen used as anchor currencies, given their importance being the major trading partners with the ASEAN countries and being the global demand currencies. This study employed the Autoregressive Distributed Lag (ARDL) procedure to examine several objectives. In general, this study found that OCA criteria have played an important role in explaining the bilateral exchange rate volatility. In addition, several financial factors were found to have significant contribution in determining exchange rate variation. Furthermore, the inclusion of Currency Control (CC) was found to have the expected negative impact on exchange rate volatility (ERV) in both types of anchor currencies namely; US Dollar and Japanese Yen.